Structures, dynamics, and hydrogen-bond interactions of antifreeze proteins in TIP4P/Ice water and their dependence on force fields. - Hwankyu Lee (PLoS ONE)
Tenebrio molitor antifreeze protein (TmAFP) was simulated with growing ice-water interfaces at a realistic melting temperature using TIP4P/Ice water model. To test compatibility of protein force fields (FFs) with TIP4P/Ice water, CHARMM, AMBER, and OPLS FFs were applied. CHARMM and AMBER FFs predict more β-sheet structure and lower diffusivity of TmAFP at the ice-water interface than does OPLS FF, indicating that β-sheet structure is important for the TmAFP-interface binding and antifreeze activity. In particular, CHARMM FF more clearly distinguishes the strengths of hydrogen bonds in the ice-binding and non-ice-binding sites of TmAFP than do other FFs, in agreement with experiments, implying that CHARMM FF can be a reasonable choice to simulate proteins with TIP4P/Ice water. Simulations of mutated TmAFPs show that for the same density of Thr residues, continuous arrangement of Thr with the distance of 0.4~0.6 nm induces the higher extent of antifreeze activity than does intermittent arrangement of Thr with larger distances. These findings suggest the choice of CHARMM FF for AFP-TIP4P/Ice simulations and help explain the relationship between Thr-residue arrangement and antifreeze activity.